Des cultures temporaires face à la forêt classée - Sébastien Caillault; Daniel Delahaye; Aziz Ballouche (Projets de Paysage)
These study analyze the role of protected areas on landscape evolution in western Burkina Faso. The analysis focuses on material change in landscape but also on representations due to those new protected areas. From aerial photography and investigations we try to understand how this area is observed by farmers. Different practices and perceptions of the landscape by farmers were identified with several examples (fallow, soil and agricultural change). Access to land is strongly linked to local context (social position of the individual and land pressure) and influenced practices and representations of landscape. Despite the significant changes we observed shapes and behaviors (housing, temporary crop, sacred woods ...) showing the importance of local dynamics in these Bwa area.